Corporate Social Responsibility in a Mixed Oligopoly - Luca Lambertini; Alessandro Tampieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
This paper investigates how CSR firms influence a Cournot oligopoly with pollution. We define as CSR a firm that takes into account not only its profits but also internalises its own share of the externality and is sensitive to consumer surplus. The CSR firm obtains higher profits compared to profit-seeking firms. Also, the presence of at least one CSR firm improves social welfare and makes the first best Pigouvian taxation more lenient for Cournot firms. Finally, the CSR firm may induce the other firms to invest in green technology.
Keywords: H23; L13; O31; 330